2019
DOI: 10.1042/bsr20181260
|View full text |Cite|
|
Sign up to set email alerts
|

Yanghe Huayan decoction inhibits the capability of trans-endothelium and angiogenesis of HER2+ breast cancer via pAkt signaling

Abstract: Background: Yanghe Huayan Decoction (YHD), a traditional Chinese medicine, is one of the most common complementary medicine currently used in the treatment of breast cancer (BC). It has been recently linked to suppress precancerous lesion and tumor development. The current study sought to explore the role of YHD on trans-endothelium and angiogenesis of BC. Methods: HER2+ BC cells were treated with YHD, Trastuzumab, or the combination in vitro and in vivo to compare the effects of them on trans-endothelium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The latest evidence shows that TCM-assisted therapy based on Yanghe Decoction is one of the most common adjuvant therapy schemes for antimalignant tumor treatment. A previous study [ 16 ] reported that Yanghe Decoction inhibited angiogenesis and epithelial-mesenchymal transition of human epidermal growth factor receptor 2 (HER2) positive breast cancer through the Akt pathway. Besides the remarkable part of Yanghe Decoction in anticancer management, it also plays an effective antiinflammatory part in the progression of some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The latest evidence shows that TCM-assisted therapy based on Yanghe Decoction is one of the most common adjuvant therapy schemes for antimalignant tumor treatment. A previous study [ 16 ] reported that Yanghe Decoction inhibited angiogenesis and epithelial-mesenchymal transition of human epidermal growth factor receptor 2 (HER2) positive breast cancer through the Akt pathway. Besides the remarkable part of Yanghe Decoction in anticancer management, it also plays an effective antiinflammatory part in the progression of some diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Yanghe Huayan decoction significantly restrained BC cell invasion and angiogenesis. 34 Xiao tan Jieyu Decoction discovered that this recipe can block the development of tumors and decrease the occurrence of BC and can also inhibit PI3K/AKT signal transduction pathway to effectively reduce the development of BC lesions. 35 …”
Section: Tcm In the Therapy Of Bcmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is considered to be a natural adjuvant therapy, especially in improving clinical symptoms, prolonging the survival of patients, and regulating immune functions [5, 6]. Yanghe decoction (YHD) is a traditional Chinese anti‐tumor medication and consists of eight herbal medicines, including Rehmanniae Radix Praeparata , Colla Cornus Cervi , Cinnanmomi Cortex , Sinapis semen , Ephedra Herba , Zingiber officinale Roscoe , Bolbostemma paniculatum , and Licorice .…”
Section: Introductionmentioning
confidence: 99%
“…Modern medical practices reveal that YHD and the extract from the ingredients of YHD could exert anti‐tumor effect on BC [7, 8]. YHD and Yanghe Huayan decoction can exert anti‐tumor and immunomodulatory effects on BC via JAK/STAT and pAkt signaling pathways, respectively [6]. Sinapine and tubeimoside‐1, the bioactive compounds in Sinapis semen and Bolbostemma paniculatum , exhibit reversed multidrug resistance and suppress metastasis in BC through NF‐κB activation [7,8].…”
Section: Introductionmentioning
confidence: 99%